Long-Term Vegetation Dynamics in a Megadiverse Hotspot: The Ice-Age Record of a Pre-montane Forest of Central Ecuador - Montoya, Encarni; Keen, Hayley F.; Luzuriaga, Carmen X.; Gosling, William D. (Frontiers in Plant Science, 2018)
Tropical ecosystems play a key role in many aspects of Earth system dynamics currently of global concern, including carbon sequestration and biodiversity. To accurately understand complex tropical systems it is necessary to parameterise key ecological aspects, such as rates of change, dynamism, resilience or stability. To obtain a long-term (>50 years) perspective on these ecological aspects we must turn to the fossil record. However, collecting continuous sedimentary archives in the lowland tropics is often difficult due to the active landscape processes, with potentially frequent volcanic, tectonic and/or fluvial events confounding sediment deposition, preservation and recovery. One of the first lowland Amazonian locations from which palaeoecological data were obtained was an outcrop near Mera (Ecuador). Mera was discovered, and analysed, by Paul Colinvaux in the 1980’s, but his interpretation of the data as indicative of a forested glacial period were criticised based on the ecology and age control. Here we present new palaeoecological data from a lake located less than 10 km away from Mera. Sediment cores raised from Laguna Pindo (1250 m asl; 1o27’S, 78o05’W) have been shown to span the late last glacial period (50 to 13 cal kyr BP). The palaeoecological information obtained from Laguna Pindo indicate that the region was characterised by a relatively stable plant community, formed by taxa nowadays common at mid and high elevations. Miconia was the dominant taxa until around 30 cal kyr BP, when it was replaced by Hedyosmum, Asteraceae and Ilex among other taxa. Heat intolerant taxa including Podocarpus, Alnus, and Myrica peaked around the onset of the Last Glacial Maximum (c. 21 cal kyr BP). The results obtained from Laguna Pindo support Colinvaux’s hypothesis that glacial cooling resulted in a reshuffling of taxa in the region but did not lead to a loss of the forest structure. Wide tolerances of of the plant species occurring to glacial temperature ranges and cloud formation have been suggested to explain Pindo forest stability. This scenario is radically different than the present situation, so vulnerability of the tropical pre-montane forest is highlighted to be increased in the next decades.